2018
DOI: 10.3390/ma11030432
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic-Cyclicgraphene: A New Two-Dimensional Semiconducting Carbon Allotrope

Abstract: A potentially new, single-atom thick semiconducting 2D-graphene-like material, called Anisotropic-cyclicgraphene , has been generated by the two stage searching strategy linking molecular and ab initio approach. The candidate was derived from the evolutionary-based algorithm and molecular simulations was then profoundly analysed using first-principles density functional theory from the structural, mechanical, phonon, and electronic properties point of view. The proposed polymorph of graphene (rP16-P1m1) is mec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…The measured lattice constant for SL 1H-MoS 2 a=3.157 Å and average height (vertical separation between S atoms) h=3.116 Å [50], while that calculated with the local density approximation (LDA) a=3.144 Å, h=3.111 Å, with the classical Perdew-Burke-Ernzerhof (PBE) generalised gradient approximation (GGA) a=3.220 Å, h=3.121 Å and with the modified Perdew-Burke-Ernzerhof GGA for solids (PBEsol) a=3.165 Å, h=3.120 Å, a similar trend can also be observed in other papers [12,51]. Once again, it was confirmed that the PBEsol is the overall best performing XC functional for identifying the structural and mechanical properties [4,52,53] and thus all subsequent calculations will use PBEsol XC functional.…”
Section: Resultssupporting
confidence: 78%
“…The measured lattice constant for SL 1H-MoS 2 a=3.157 Å and average height (vertical separation between S atoms) h=3.116 Å [50], while that calculated with the local density approximation (LDA) a=3.144 Å, h=3.111 Å, with the classical Perdew-Burke-Ernzerhof (PBE) generalised gradient approximation (GGA) a=3.220 Å, h=3.121 Å and with the modified Perdew-Burke-Ernzerhof GGA for solids (PBEsol) a=3.165 Å, h=3.120 Å, a similar trend can also be observed in other papers [12,51]. Once again, it was confirmed that the PBEsol is the overall best performing XC functional for identifying the structural and mechanical properties [4,52,53] and thus all subsequent calculations will use PBEsol XC functional.…”
Section: Resultssupporting
confidence: 78%
“…The measured lattice constant for SL 1H-MoS a = 3.157 Å and average height (vertical separation between S atoms) h = 3.116 Å [ 50 ], while that calculated with the local density approximation (LDA) a = 3.144 Å, h = 3.111 Å, with the classical Perdew–Burke–Ernzerhof (PBE) generalised gradient approximation (GGA) a = 3.220 Å, h = 3.121 Å and with the modified Perdew–Burke–Ernzerhof GGA for solids (PBEsol) a = 3.165 Å, h = 3.120 Å, a similar trend can also be observed in other papers [ 12 , 51 ]. Once again, it was confirmed that the PBEsol is the overall best performing XC functional for identifying the structural and mechanical properties [ 4 , 52 , 53 ] and thus all subsequent calculations will use PBEsol XC functional.…”
Section: Resultsmentioning
confidence: 93%
“…The major disadvantages of graphene are the lack of a band gap in the electronic spectrum, its susceptibility to oxidative environments and that it has some toxic properties. That is why scientists and engineers, beyond ordinary human curiosity, have begun to look for materials free of these deficiencies [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the confidence of the calculations as an exchange-correlation (XC) functional, three approximations were used: local density approximation (LDA) [32,33], classical Perdew-Burke-Ernzerhof (PBE) generalised gradient approximation (GGA) [34] and modified Perdew-Burke-Ernzerhof GGA for solids (PBEsol) [35]. There is a strong view that the PBEsol is the overall best performing XC functional for identifying the structure and elastic properties [36][37][38].…”
Section: Methodsmentioning
confidence: 99%